Poverty and aspirations failure - Dalton, Patricio S.; Mani, Anandi; Ghosal, Sayantan (2016)
We study the macroeconomic implications of time-varying precautionary savings within a general equilibrium model with borrowing constraints, aggregate shocks and uninsurable idiosyncratic unemployment risk. Our framework generates limited cross-sectional household heterogeneity as an equilibrium outcome, thereby making it possible to analyse the role of precautionary saving over the business cycle in an analytically tractable way. The time-series behaviour of aggregate consumption generated by our model is closer to the data than that implied by the hand-to-mouth and representative-agent models, and it is comparable to that produced by the Krusell and Smith (1998) model. - Reproduced.
Keywords: Poverty